Model of Problem-Based Learning in Geography: Focusing on Societal Dynamics to Enhance Spatial Thinking Skills - Fadjarajani Siti; As’ari Ruli; Putri Anita Eka (E3S Web of Conferences)
This article explores how problem-based learning (PBL) can enhance geography education by improving spatial thinking through social dynamics. Spatial thinking is crucial for understanding geography’s social complexity and advancing STEM education quality. Geographic Information Systems (GIS) and the Spatial-Based Learning (SBL) model are utilized to develop these skills, vital for disaster management and emergencies. The study employs participatory action research, involving students, teachers, and communities in solving real-world problems, assessing PBL’s impact on spatial thinking in geography education. The community dynamics framework emphasizes active student engagement with local communities, deepening their geographical understanding. Internet-based GIS technology facilitates collaborative spatial data analysis, promoting civic participation and social responsibility. PBL in studying societal dynamics fosters critical thinking, relevance, and authenticity in learning. By addressing real-world challenges, students improve critical thinking, problem-solving, and motivation. In conclusion, integrating PBL in geography education, focusing on societal dynamics to enhance spatial thinking, significantly improves teaching effectiveness and develops critical thinking skills crucial for geographic education.